A Facile and Green Nitration of Easily-Hydrolyzed Aromatic Compounds Based on Direct Filtration and H2SO4 Recycling - Li, Runlai; Zhang, Zhenming; Ji, Jiangyu; Li, He; Liu, Chi; Li, Shu-an (Letters in Organic Chemistry, 2023)
The conventional mixed acid nitration of aromatic hydrocarbons has been extensively applied in the industry, but usually, it is not highly selective and may cause environmental concerns regarding the disposal of large volumes of mixed acids. This paper proposes a new method of orientational para-nitration of easily hydrolyzable aromatic compounds. Under the optimized reaction conditions, the easily hydrolyzed aromatic compounds were nitrated in the H2SO4-HNO3-H3PO4 system to yield paste-like products. And the product could be directly filtered out from the mixed acid, avoiding a large amount of waste liquid caused by pouring the reaction mixture into ice water by the traditional post-treatment method. The selectivity and yield of nitration by this method have been improved, and the mother liquor could be reused, thereby reducing the cost and pollution.
Keywords: filtration